Inter-generational distribution of resources in a model of economic growth: Taking the land vs. food trade-off into account - Frauke Voosholz (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2013)
This paper considers a model with three overlapping generations of which only the middle one is able to work. There is a trade-off between food and bio-fuel pro- duction. We try to study this trade-off, its influence on economic growth and on resource consumption. The paper should state that even, if the current generation has the total autonomy of decision about the usage of all resources, they will never use them completely. The memebers of the current generation will always leave some resources for production because in the phase of retirement they depend on the income of the next generation, the latter paying back the credit obtained when beeing young. Furthermore, it states that as long as land is an essential input for producing the final product (including food) the amount of land devoted to bio-fuel production will not raise endlessly. The pure consumption loan model by Samuelson (1958) serves as basis for our Overlapping-Generations-Model, which we will integrate into a model of endogenous economic growth with resources, exogenous technical progress and land as a further input. For realization of the optimal consumption pattern, which leads to the maximum of utility, individuals have to make four decisions. They have to commit themselves on the exploitation rate of the non-renewable resource and on the amount of renewable resource used for production. Coincidentally, the allocation of land, necessary for food production and for renewable resource regeneration, and the amount of leisure time devoted for resource production have to be determined. The results are confirmed by numerical examples and will be reviewed by empirical data.
Keywords: D91; O13; Q24; Q32; 330; economic growth; overlapping generations; non-renewable resources; renewable resources; land vs. food trade-off